Nurses’ Expression of Transcultural Care to Patients With Cancer: A Phenomenological Study of the Philippines Context - Ismail, Suhartini; Salinda, Ma. Theresa; Fornolles, Daryl Jake (Fakultas Ilmu-ilmu Kesehatan, 2023)
Transcultural health care involves providing individualized and holistic health care to clients across cultures. Understanding and learning the differences in each culture will promote optimum care levels, especially for patients with cancer. This study describes nurses' expression of transcultural care to patients with cancer. This is a descriptive phenomenological study of nurses' expression in transcultural care to patients with cancer. A total of 11 participants were selected by using purposive sampling. Data was gathered from in-depth interviews among nurses who took care of patients with cancer via an online platform. Data analysis used Colaizzi's thematic analysis. The study’s trustworthiness was established by its credibility, dependability, confirmability, and transferability. Four major themes were generated in this study: (1) cultural congruent care, (2) cultural and communication competency, (3) integrity as a vital aspect of respect and consideration of other cultures, and (4) challenges nurses face when a caring for patients with cancer and their transcultural and patient-driven solutions. Caring is about giving patients hope, love, and services based on their cultural sensitivity. Connecting and interacting effectively with people from different cultural backgrounds is essential in today's globalized society.